2021
DOI: 10.1155/2021/6633271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Self-Reported Work-Related Lower Back Pain and Its Associated Factors in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Introduction. Low back pain is the commonest musculoskeletal disorder affecting every socioeconomic group of the world’s population. The lifetime risk of developing low back pain is about 60%–80%. The pooled prevalence and associated factors of low back pain have not yet been determined in Ethiopia. Thus, this study was aimed at assessing the overall prevalence of low back pain and its associated factors in Ethiopia. Methods. A systematic search of PubMed, Scopus, Science Direct, and Google Scholar for observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 86 publications
0
14
0
1
Order By: Relevance
“…Finally, six systematic reviews with meta-analyses were included. (Jegnie & Afework, 2021; Kasa et al, 2020; Mengistu et al, 2021, 2022; Morris et al, 2018; Tesfaye et al, 2023) Manually, we found four extra studies. However, these studies did not check our inclusion criteria and were excluded.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Finally, six systematic reviews with meta-analyses were included. (Jegnie & Afework, 2021; Kasa et al, 2020; Mengistu et al, 2021, 2022; Morris et al, 2018; Tesfaye et al, 2023) Manually, we found four extra studies. However, these studies did not check our inclusion criteria and were excluded.…”
Section: Resultsmentioning
confidence: 98%
“…Low back pain: the pooled annual prevalence of low back pain was from higher to lower prevalence percentage: 64.07% (95%CI 58.68–69.46), I 2 = 94.2% (k= 19, N= 6,110, specific population: nurses),(Kasa et al, 2020) 59.0% (95%CI 52.0-65.0%), I 2 = 96.27% (k= 11, N= 5,805, specific population: schoolteachers),(Tesfaye et al, 2023) 57% (95%CI 51-63%), I 2 = unreported (k= 34, N= 17,210),(Morris et al, 2018) 54.2% (95%CI 48.2-60.0%), I 2 = 96.78% (k= 19, N= 8,993, specific country: Ethiopia),(Mengistu et al, 2021) and 54.05% (95%CI 48.14–59.96), I 2 = 97.6% (k= 24, N= 10,447, specific country: Ethiopia) ( Figure 7 ). (Jegnie & Afework, 2021) Upper back pain: the pooled annual prevalence of upper back pain was: 27.1% (95%CI 18.4-37.9), I 2 = 98.029% (k= 10, N= 4,284, specific country: Ethiopia) ( Figure 7 ). (Mengistu et al, 2021) Elbow pain: the pooled annual prevalence of elbow pain was: 19.7% (95%CI 12.3-30.1%), I 2 = 98.16% (k= 10, N= 4,294, specific country: Ethiopia) ( Figure 8 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, there has been no study investigating nurses' ability to prevent occupational low back pain utilizing a scientific scale, limiting the value of assessing competency in establishing health promotion programs. Therefore, this study attempted to address three scientific questions: (1) what is the ability of nurses to prevent occupational low back pain? (2) which factors affect nurses' ability?…”
Section: Resultsmentioning
confidence: 99%
“…Occupational low back pain, defined as pain or discomfort from the lower edge of the 12th rib of the pelvis caused by occupational causes, has become one of the three primary occupational health concerns ( 1 ). Compared to other professions, nurses have a higher prevalence of occupational low back pain given the suffering of chronic lumbar strain and elevated spinal pressure at work ( 2 ), especially since the outbreak of the COVID-19 pandemic, which has increased the nurses' workloads ( 3 ).…”
Section: Introductionmentioning
confidence: 99%